Mushroom Intake and Risk of Epithelial Ovarian Cancer in Southern Chinese Women - Lee, Andy; Pasalich, Maria; Su, Dada; Tang, Li; Tran, D.; Binns, Colin (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: This study aimed to investigate the association between mushroom consumption and risk of epithelial ovarian cancer in southern Chinese women.METHODS: A hospital-based case-control study was undertaken in Guangzhou, Guangdong Province, from 2006 to 2008. Participants were 500 incident patients with epithelial ovarian cancer and 500 controls, with a mean (SD) age of 59 (6) years. Information on habitual mushroom consumption was obtained by face-to-face interview using a validated and reliable food frequency questionnaire. Unconditional logistic regression analyses were performed to assess the association between mushroom intake and the ovarian cancer risk.RESULTS: The patients with ovarian cancer consumed less mushrooms (mean [SD], 28.48 [37.45] g/d) than did controls (mean [SD], 30.75 [41.85] g/d). Apparent reductions in cancer risk were found at high levels of intake, especially for the common white button mushroom with adjusted odds ratios 0.68 (95% confidence interval, 0.52-0.89) for women consuming more than 2 g per day relative to those who consume less than that (P = 0.005). Decreases in risk at high levels of intake were also observed for serous and mucinous subtypes of epithelial ovarian tumors.CONCLUSIONS: Intake of mushrooms, particularly white button mushroom, seemed to be inversely associated with the incidence of epithelial ovarian cancer in southern Chinese women.